Two distinctive new species of Commicarpus (Nyctaginaceae) from gypsum outcrops in eastern Ethiopia. Issue 3 (September 2016) - Friis, Ib; Gilbert, Michael; Weber, Odile; Demissew, Sebsebe
Summary During field trips in 2013 and 2014, two distinctive plants belonging to the genusCommicarpus were collected in the Lele Hills, Bale Zone, eastern Ethiopia, on outcrops of sedimentary rock belonging to the Gorrahei Formation with high contents of gypsum. The plants are here described as two new species:Commicarpus macrothamnus Friis & O. Weber sp. nov. is unique among all hitherto described species ofCommicarpus, being a robust free-standing shrub, almost a small tree up to 3½ m high, with woody stems up to c. 12 cm in diam.Commicarpus leleensis Friis & Sebsebe sp. nov. is also unusual inCommicarpus, being a small self-supporting shrub to 0.8 (– 1) m high. Both new species occur in small populations with restricted distribution; models based on the available information show that the potential distribution is also restricted.C. macrothamnus is here evaluated as Vulnerable (VU), whileC. leleensis, only known from the type, should remain Data Deficient (DD). Outcrops of gypsum with restricted-range species are well known from eastern Ethiopia and Somalia, but the locality with the two new species ofCommicarpus is the most north-western and one of the highest sites recorded so far for gypsum endemics.